2005
DOI: 10.1182/blood-2004-10-3927
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A and tacrolimus, but not rapamycin, inhibit MHC-restricted antigen presentation pathways in dendritic cells

Abstract: The main targets for the immunosuppressive calcineurin inhibitors, cyclosporin A (CsA) and tacrolimus, have been considered to be activated T cells, but not antigen-presenting cells. Here we demonstrate that CsA and tacrolimus, but not rapamycin, inhibit major histocompatibility complex (MHC)-restricted antigen presentation in dendritic cells (DCs). Microencapsulated ovalbumin (OVA) was efficiently captured, processed, and presented on both class I MHC molecules IntroductionDendritic cells (DCs) play a key ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 31 publications
5
86
1
1
Order By: Relevance
“…As shown here, the treatment of DCs with rapamycin augments a Th1 response ( Figure 7A). Because rapamycin does not alter antigen uptake and presentation, 35 or the expression level of costimulatory molecules such as CD80 and CD86 in DCs, 36 the enhancement of a Th1 response by rapamycin is probably the result of the augmentation of IL-12 production. In addition, the inhibition of GSK3 by LiCl suppressed a Th1-mediated immune response against L major in vivo ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…As shown here, the treatment of DCs with rapamycin augments a Th1 response ( Figure 7A). Because rapamycin does not alter antigen uptake and presentation, 35 or the expression level of costimulatory molecules such as CD80 and CD86 in DCs, 36 the enhancement of a Th1 response by rapamycin is probably the result of the augmentation of IL-12 production. In addition, the inhibition of GSK3 by LiCl suppressed a Th1-mediated immune response against L major in vivo ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4). That slight reduction could be due either to some CSA-mediated impairment of Agpresenting function in the target cells themselves (34), or, more likely, to the fact that the IFN-␄ normally produced in CD8 Ï© T cell-LCL cocultures might further enhance Ag presentation by the LCL. Whatever the explanation for this slight effect, the overall results in conjunction with the Transwell assays clearly showed that cytokines are not the primary mechanism of T cell-mediated growth control, and instead refocused attention on a cytotoxic mechanism, perhaps through slow killing not detectable in 5-h assays.…”
Section: Discussionmentioning
confidence: 99%
“…Then, at various time points after infection, we treated the MDM with the calcineurin inhibitor FK-506 to block the transport of newly epitope-loaded MHC-II molecules to the cell surface. FK-506 has been previously shown to block presentation of both exogenous and endogenous antigen while not interfering with T cell cytokine secretion (24,25). Therefore, addition of 4 nM FK-506 effectively paused MHC-II antigen presentation, allowing us to assess the kinetics of MHC-II antigen presentation in detail.…”
mentioning
confidence: 99%